Possible Implications of Artificial Intelligence on Obstetrics and Gynecology and Medicine in the Next Few Decades - Michael H. Dahan; David Ardman; Seang Lin Tan (IMR Press, 2023)
Artificial intelligence will change work for most people in significant and unexpected fashions in the next few decades. A change similar to that seen with the industrial revolution of the 19th century. Certain jobs will cease to exist while new employment will be created. The implication of this transformation in medicine and obstetrics and gynecology in particular needs discussion, as it stands it is anxiety-provoking. Artificial intelligence will have implications on the number of physicians needed in certain specialties, the workloads of those physicians, and the ease of accessing information. In the field of reproductive endocrinology, artificial intelligence is already being used to select embryos with the greatest potential for implantation. Who will develop that technology and the drivers for development will also be considered. Physicians, insurance companies, and other funders of health care need to be informed to anticipate and prepare for these changes. As such we will discuss anticipated changes in the near future to be initiated by artificial intelligence, we anticipate physician quality of life will improve while the demonstrated anxiety is unfounded.